The Role of Arbitration in Resolving Electronic Disputes - Between Theory and Practice (NTU journal for Administrative and Human Sciences (JAHS), 2022)
Praise be to God who sent down the Book to his servant and did not make him crooked, and I pray and greet our master and leader Muhammad bin Abdullah, and his family and all his companions, and then:We have become all in the era of speed, whether we are or not, the age of technology and the technician of information and the trade exchange between countries with some of them, and with individuals also .. It is presented to search for control over the internet and the e -mail in all Dealing directly with online arbitration as a method for resolving disputes for both for the year 1952 AD, the Unified Agreement for the Investment of Arab Capital in the Arab Countries for the year 1981 AD, the Riyadh Agreement for Judicial Cooperation for the year 1983 AD, and others